Histological and Radiological Correlation in the Diagnosis of Bone Tumors - ZERTAJ KASHIF, IJAZ WARIS, *ASIMA NAZ (Journal of Fatima Jinnah Medical University, 2018)
Objective: To Determine the sensitivity, specificity, positive predictive value and negative predictive value of radiological results of bone tumors, taking histological findings as the gold standard. Study design: Descriptive case series Subjects & methodology: Thirty cases of clinically suspected and with radiological evidence of bone tumors were included in this study. The specimens were sent to the Histopathology Department, fixed in 10% formaline. Results: The peak age incidence of bone tumors was between 10 to 20 years age groups, with mean age 22.87±12.13, while minimum number of patients were above 40 years age. The study revealed more males 20 cases (66.7%) with bone tumors than females 10 (33.3%). Histopathologically, 12 tumors were malignant and radiology suggested 10 tumors as malignant, Sensitivity, specificity, diagnostic accuracy, positive predictive value (PPV) and negative predictive value (NPV) of radiological findings were found as 83.3%, 100.0%, 93.3%, 100.0% and 90.0%, respectively. Conclusion: The histopathology appears slightly more accurate compared to radiology in typing, grading and staging of the bone tumors and remains the gold standard.